Evaluación de seis tipos de protectores en el enfunde de racimo de banano (Musa sapientum.) en la finca Manguila del Cantón La Maná año 2010-2011 - Enríquez Tovar, Limber Eduardo (2011)
This research was carried out in the dry season of 2010 on the farm "Manguila" (Agricultural Enriquez). . Located at the geographic coordinates 00 º 55 '45''latitude and 79 º 13' 55''longitude. In La Mana town. The main objective was to reduce waste and improve the quality and quantity of the fruit of banana (Musa sapientum.) Through the use of hand protectors of the cluster, and specifically to determine the most appropriate type of protector for maximum return on Banana production quality….